Gondang Function at the Patarias Debata Mulajadi Nabolon Ritual Ceremony - Limbong Marison Aritonang; Asmyta Surbakti; Mauly Purba (Gondang: Jurnal Seni dan Budaya, 2026)
This study examines the function of gondang bolon music in the Patarias Debata Mulajadi Nabolon ritual, an ancestral ceremony performed once every four years by descendants of Ompu Mamontang Laut Ambarita in Sihaporas Village, Pematang Sidamanik District, Simalungun Regency, North Sumatra. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation during the ritual performance held on 22-24 October 2022. Alan P. Merriam's theory of the uses and functions of music was applied to examine how gondang bolon mediates communication between the Toba Batak community and Mulajadi Nabolon, the supreme creator in their traditional belief system. The findings show that gondang bolon performs at least seven interrelated functions within the ritual: accompanying the ceremonial sequence, guiding the tortor dance and ritual movement, communicating symbolic and religious meaning, expressing emotion, reinforcing social interaction, strengthening communal solidarity, and sustaining cultural continuity across generations. Performed by an ensemble of five taganing, one gordang, three to four ogung, one hesek, and a sarune bolon, gondang bolon proves to be far more than musical accompaniment: each tone produced functions as an intermediary that carries offerings, prayers, and petitions from the community to the spiritual realm. Comparison with related studies of gondang sabangunan in other Toba Batak ritual contexts confirms that these functions recur across ceremonies while taking locally specific forms in Sihaporas. The study concludes that gondang bolon is central to both the sacredness and the social cohesion of the ritual, and recommends further ethnomusicological research on its musical structure and long-term sustainability.